Association between thickness of subcutaneous fat and incisional surgical site infection following appendectomy: a systematic review and meta-analysis on observational studies - Mansour Bahardoust; Yasaman Asadi Kalbibaki; Sara Shiraghaie; Shabnam Rashidi; Mohammadsadra Shamohammadi; Ali Hashemi Kiapay; Meisam Haghmoradi; Babak Goodarzy; Adnan Tizmaghz (BMC Surgery)
Abstract Background The relationship between thickness of subcutaneous fat (TSF) and surgical site infection (SSI), as one of the most common complications after appendectomy, has been inconsistent in different studies, which may be due to the low power of these studies. This meta-analysis aimed to investigate the relationship between SSI and TSF after open surgery (OS) and laparoscopic surgery (LS) in patients with appendicitis. Methods PubMed, Embase, Scopus, Google Scholar, and Web of Science databases were searched based on mesh terms to find relevant studies from the beginning of 2000 to 2024. The mean TSF during surgery was defined as exposure, and SSI after OS or laparoscopy appendectomy was defined as an outcome. The heterogeneity between studies was assessed using Cochran's Q and I2 tests. Meta-regression was employed to manage the heterogeneity. Nine studies, including 4,439 patients, were included. Results The pooled estimate from nine studies indicated that an increase in TSF was significantly associated with an increased risk of SSI(OR: 1.32, 95% CI: 1.12, 1.52, I2: 82.4%, p: 0.001). Subgroup analysis showed that TSF in patients undergoing OS was significantly associated with increased risk of SSI (OR: 1.82, 95% CI: 1.27, 2.38, I2: 84.3%, P: 0.001). In contrast, in patients undergoing LS, mean TSF was not significantly associated with increased risk of SSI (OR: 1.09, CI: 0.90, 1.28, I2: 53.1%, P: 0.001). Conclusion TSF was significantly associated with an increased risk of SSI after OS, while it was not significantly associated with an increased risk of SSI in laparoscopically operated patients. Considering TSF during surgery to choose the appropriate surgical method and post-treatment care can help prevent and reduce the risk of SSI after appendectomy.